Metritis in dairy cows: risk factors and reproductive performance - Giuliodori, M. J. (2013)
The objectives of this study were to assess the risk factors for metritis, its effects on milk yield and on reproductive efficiency, and the efficacy of ceftiofur therapy in Holstein dairy cows. Cows (N = 303) from a commercial dairy herd in Argentina were studied. Cows were body condition scored and tail bled on days -14, 7, 21, 31, 41 and 50 relative to parturition. Cows having a watery, purulent or brown-colored, fetid vaginal discharge (VD) and rectal temperature <39.1ºC were diagnosed as having clinical metritis, and those having a similar VD and rectal temperature ≥ 39.1ºC were diagnosed as having puerperal metritis. Both, clinical and puerperal metritis cows were randomly assigned to control (no treatment) or ceftiofur group (2.2 mg/kg x 3 consecutive days). Cure was declared if clear VD was observed 21 days in milk (DIM). Blood samples were analyzed for non‐esterified fatty acids, -hydroxy butyric acid and blood urea nitrogen using commercial kits and insulin-like growth factor-1, insulin, and leptin by RIA. Data were analyzed with PROC MIXED, GENMOD, PHREG and LIFETEST from SAS. The risk for metritis increased with abnormal calving (AOR [adjusted odds ratio] = 2.58, 95% CI = 1.189 to 5.559, P = 0.008), and as prepartum NEFA levels increased (AOR = 1.001, 95% CI = 0.999 to 1.002, P = 0.177). Conversely, risk decreased as prepartum IGF-1 increased (AOR = 0.65, 95% CI = 0.349 to 1.219, P = 0.144). Cows having both, clinical and puerperal metritis produced less milk by 90 DIM than the normal cows (2,236  172 vs. 2,367  77 vs. 2,647  82 kg, respectively, P = 0.009). Cows with puerperal metritis had lower risk for pregnancy by 100 DIM (AOR = 0.189, 95% CI = 0.070 ? 0.479, P = 0.014), lower hazard rate for pregnancy by 150 DIM (0.753, 95% CI = 0.621 to 0.911, P = 0.014), and took longer to get pregnant (129 vs. 111 vs. 109 days, for puerperal metritis, clinical metritis and normal cows, respectively, P = 0.015). Ceftiofur had neither effect on cure rate nor on milk yield but increased the risk for TAI (AOR = 2.126, 95% CI = 0.983 to 4.597, P = 0.055) and for pregnancy at TAI (AOR = 2.688, 95% CI = 0.687 to 10.832, P = 0.142), and reduced the risk for reproductive cull (AOR = 0.121, 95% CI = 0.014 to 1.066, P = 0.057). In conclusion, abnormal calving and negative energy balance increase the risk for metritis. Metritis, especially the puerperal one, reduces both, milk production and reproductive efficiency. Finally, the likelihood for having a normal vaginal discharge (indicative of cure) increases 2.6 % for every day of increase in postpartum time and is 2 times higher for cows with clinical metritis than for those with puerperal metritis.